Single-level Lumbar Fusion Versus Total Joint Arthroplasty: A Comparison of 1-year Outcomes. Issue 23 (1st December 2022) - Minetos, Paul D.; Karamian, Brian A.; Levy, Hannah A.; Canseco, Jose A.; Robinson, William A.; D'Antonio, Nicholas D.; Lambrechts, Mark J.; Chisari, Emanuele; Kaye, I. David; Kurd, Mark F.; Rihn, Jeffrey A.; Kepler, Christopher K.; et al.
Abstract : Introduction: Primary hip and knee arthroplasty represent two of the most successful orthopaedic surgical interventions in the past century. Similarly, lumbar fusion (LF) remains a valuable, evidence-based option to relieve pain and disability related to spinal degenerative conditions. This study evaluates the relative improvements in 1-year health-related quality of life (HRQOL) measures among patients undergoing primary single-level LF, primary total hip arthroplasty (THA), and primary total knee arthroplasty (TKA). Methods: Patients older than 18 years who underwent primary single-level posterior LF (posterolateral decompression and fusion with or without transforaminal lumbar interbody fusion, involving any single lumbar level), TKA, and THA at a single academic institution were retrospectively identified. Patient demographics and surgical characteristics were collected. HRQOL measures were collected preoperatively and at 1-year postoperative time point including Short-Form 12 Physical Component Score (PCS) and Mental Component Score (MCS) along with subspecialty-specific outcomes. Results: A total of 2, 563 patients were included (346 LF, 1, 035 TKA, and 1, 182 THA). Change in MCS-12 and PCS-12 after LF did not vary markedly by preoperative diagnosis. LF patients had a significantly lower preoperative MCS-12 (LF: 50.8, TKA: 53.9, THA: 52.9, P < 0.001), postoperative MCS-12 (LF: 52.5, TKA: 54.8, THA: 54.5, P < 0.001), postoperative PCS-12 (LF: 40.1, TKA: 44.0, THA: 43.9, P < 0.001), ΔPCS-12 (LF: 7.9, TKA: 10.8, THA: 11.9, P < 0.001), and PCS-12 recovery ratio (LF: 10.7%, TKA: 15.1%, THA 16.6%, P < 0.001) compared with TKA and THA patients. In regression analysis, both TKA and LF were found to be independently associated with a smaller ΔPCS-12 improvement (TKA: β = −1.36, P = 0.009; LF: β = −4.74, P < 0.001) compared with THA. TKA (β = −1.42, P = 0.003) was also independently associated with a smaller ΔMCS-12 improvement compared with THA. Conclusions: Patients undergoing single-level LF, TKA, and THA demonstrate notable improvements in HRQOL outcomes at 1 year postoperatively compared with preoperative baseline scores. The greatest improvements were found among THA patients, followed subsequently by TKA and LF patients. Both LF and TKA were independently associated with markedly less improvement in physical disability at 1 year postoperatively compared with THA. Study Design: Retrospective Cohort Study